2019
DOI: 10.1186/s13046-019-1425-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of alternative TrkAIII splicing in Merkel cell carcinoma: a potential oncogenic mechanism and novel therapeutic target

Abstract: BackgroundMerkel cell carcinomas (MCCs) are rare, aggressive, therapeutically-challenging skin tumours that are increasing in incidence and have poor survival rates. The majority are caused by genomic Merkel cell polyomavirus (MCPyV) integration and MCPyV T-antigen expression. Recently, a potential oncogenic role for the tropomyosin-related tyrosine kinase A receptor (TrkA) has been proposed in MCC. Alternative TrkAIII splicing is a TrkA oncogenic activation mechanism that can be promoted by SV40 large T-antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 40 publications
8
21
0
Order By: Relevance
“…Furthermore, analysis of potential promoters of alternative ∆ exon 6-7 TrkAIII splicing in NB cells identified the polyomavirus simian virus 40 (SV40) large T-antigen [30], raising the possibility that closely related polyomavirus MCPyV T-antigens may also promote alternative ∆ exon 6-7 TrkAIII splicing in MCPyV-positive MCCs. This hypothesis was supported in our pilot study [28], which detected a close relationship between MCPyV T-antigen expression and alternative ∆ exon 6-7 TrkAIII splicing in FFPE MCC tissues, characterising a new MCC subset and identifying a novel potential MCPyV oncogenic mechanism and therapeutic target (Figure 1). This, however, could not be fully verified due to the poor RNA quality and difficulty in protein extraction from FFPE tissue [28].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, analysis of potential promoters of alternative ∆ exon 6-7 TrkAIII splicing in NB cells identified the polyomavirus simian virus 40 (SV40) large T-antigen [30], raising the possibility that closely related polyomavirus MCPyV T-antigens may also promote alternative ∆ exon 6-7 TrkAIII splicing in MCPyV-positive MCCs. This hypothesis was supported in our pilot study [28], which detected a close relationship between MCPyV T-antigen expression and alternative ∆ exon 6-7 TrkAIII splicing in FFPE MCC tissues, characterising a new MCC subset and identifying a novel potential MCPyV oncogenic mechanism and therapeutic target (Figure 1). This, however, could not be fully verified due to the poor RNA quality and difficulty in protein extraction from FFPE tissue [28].…”
Section: Introductionsupporting
confidence: 56%
“…This hypothesis was supported in our pilot study [28], which detected a close relationship between MCPyV T-antigen expression and alternative ∆ exon 6-7 TrkAIII splicing in FFPE MCC tissues, characterising a new MCC subset and identifying a novel potential MCPyV oncogenic mechanism and therapeutic target (Figure 1). This, however, could not be fully verified due to the poor RNA quality and difficulty in protein extraction from FFPE tissue [28].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…42 Finally, novel agnostic therapeutic agents, such as larotrectinib and entrectinib, that inhibit mutation and deletion-activated Trk oncogenes, elicit remarkable durable responses in a wide range of advanced stage Trkfusion oncogene-driven cancers, including melanoma. 43…”
Section: Discussionmentioning
confidence: 99%
“…A small study ( n = 10) revealed that MCCP tumors may tend to display activating alternative splicing of NTRK1 mRNA. [ 23 ] Notably, none of the samples with NTRK1 SNVs in our cohort were MCCP. If TrkA activity is a key oncogenic pathway for MCCP tumors, we could speculate that NTRK1 alterations may confer an “MCCP-like” phenotype onto MCCN tumors by activating this pathway.…”
Section: Discussionmentioning
confidence: 99%